Pengaruh Pengetahuan Investasi Terhadap Minat Mahasiswa Berinvestasi Pada Galeri Investasi Syariah FAI UMSU - Isha Puri Kaniza; Khairunnisa Khairunnisa (Jurnal Manajemen Akuntansi (JUMSI), 2023)
This study aims to determine and analyze the influence of investment knowledge on student interest in investing in Sharia investment Gallery FAI UMSU. The type of research in this study is quantitative with associative approach. The population of this study is FAI students who are registered in the Sharia investment Gallery. Sample selection method using saturated smpling, the number of samples used is 33 sample data. Prior to the study, first conducted instrument trials with validity test and reliability test. Prerequisite test analysis includes normality test. Data analysis method using simple linear regression. investment knowledge of 3.787 for 5% error Test 2 parties and df = n-k (33-2 = 31), obtained ttable 2.039. In this case count = 3.787 > table = 2.039.Furthermore, it can also be seen that the probability value of T, namely sig is 0.001 while the significant level of ③ previously determined is 0.05, the sig value is 0.001 < 0.05 so that it can be concluded that investment knowledge has an effect on investment interest.